Extremely flat metal films implemented by surface roughness transfer for flexible electronics. Issue 20 (19th March 2018) - Kim, Kisoo; Kim, Sungjoo; Jung, Gwan Ho; Lee, Ilhwan; Kim, Sungjun; Ham, Juyoung; Dong, Wan Jae; Hong, Kihyon; Lee, Jong-Lam
Abstract : We present an innovative approach to fabricate an extremely flat (EF) metal film which was done by depositing metal on an extremely flat mother substrate, then detaching the metal from the substrate. Abstract : We present an innovative approach to fabricate an extremely flat (EF) metal film which was done by depositing metal on an extremely flat mother substrate, then detaching the metal from the substrate. The detached flexible metal films had a roughness that was within 2% of the roughness of the mother substrate, so EFs with R a < 1 nm could be fabricated using the surface roughness transfer method. With quantitative analysis using in situ synchrotron XPS, it was concluded that the chemical reaction of oxygen atoms with the metal film played a critical role in designing a peel-off system to get extremely flat metal films from the mother substrate. The OLED was successfully implemented on the metal film. The OLED's luminance could be increased from 15 142 to 17 100 cd m −2 at 25 mA m −2 by replacing the glass substrate with an EF copper (Cu) substrate, due to the enhanced heat dissipation during the operation. This novel method can be very useful for mass production of large scale, low-cost and high quality metal films using roll-to-roll process.